ACADEMICIAN E.V. RTVELADZE - A LIFE DEDICATED TO SCIENCE - Кобзева О. П., (TARIXIY TADQIQOTLAR, 2025)
The article is dedicated to the life of an outstanding Uzbek scientist, archaeologist, historian, orientalist - academician Edward Vasilyevich Rtveladze (1942-2022). It is dedicated to the 90th anniversary of the founding of the Faculty of History of the Mirzo Ulugbek National University of Uzbekistan, of which E.V. Rtveladze is a world-famous graduate.